ECONOMIC INPUT OF NON-WOOD FOREST PRODUCTS OF ANIMAL ORIGIN TO THE TURNOVER OF FOREST DISTRICTS IN ROMANIA - Cristian Mihai ENESCU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
In Romania, forest management is focused on wood harvesting and marketing, non-wood forest products (NWFPs) having a low importance. Even so, across the country there are more than three hundred fifty NWFPs of interest, forest fruits, mushrooms and truffles, forest seeds, game products, fish from the mountainous water, honey and tree saps being among the most common ones. The main aim of this study was to highlight the economic contribution of NWFPs of animal origin to the turnover of the forest districts in Romania. Secondly, the potential of these products was assessed by using an Analytical Hierarchy Process implemented in Expert Choice Desktop software. By using a set of eight criteria, game products proved to be more promising in comparison with honey and fish from the waters included in the national forest fund. On average, NWFPs of animal origin have a very low (less than 1%) contribution to the turnover of the forest districts in Romania. The brief multi-decision analysis could represent an alternative for the forest managers aimed at highlighting the best alternative in a chosen scenario.